2006
DOI: 10.1002/bies.20408
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities in compensation

Abstract: SummaryThe sex chromosomes of many species differ in dosage but the total gene expression output is similar, a phenomenon referred to as dosage compensation. Previously, diverse mechanisms were postulated to account for compensation in distantly related taxa. However, two recent papers present evidence that dosage compensation in Drosophila, mammals and nematodes share the property that there is an approximately two-fold upregulation of the single active X chromosome in each case.(1,2)The results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…Thus, the two effects occurring simultaneously cancel to produce dosage compensation. This type of mechanism has been recapitulated for cases of dosage compensation in Drosophila (14)(15)(16)(17) and recent evidence suggests an involvement of balance in cases of dosage compensation in plants and for sex chromosomes in Drosophila, C. elegans and mammals (18).…”
Section: Dosage Compensationmentioning
confidence: 89%
“…Thus, the two effects occurring simultaneously cancel to produce dosage compensation. This type of mechanism has been recapitulated for cases of dosage compensation in Drosophila (14)(15)(16)(17) and recent evidence suggests an involvement of balance in cases of dosage compensation in plants and for sex chromosomes in Drosophila, C. elegans and mammals (18).…”
Section: Dosage Compensationmentioning
confidence: 89%
“…On the other hand, regional dosage compensation, possibly caused by MHM, occurs in chicken but not in zebra finch. Thus, an additional (nonregional) dosage compensation mechanism may be common to both species, possibly the result of network regulatory influences that are gene-specific (Birchler et al 2006;Arnold et al 2008). …”
Section: Sex Bias and Dosage Compensation In Birdsmentioning
confidence: 99%
“…Sex chromosome dosage compensation involves diverse sexspecific mechanisms that adjust the expressed dose of genes encoded on heteromorphic sex chromosomes, to offset the sex difference in expression that would otherwise result from the sex difference in copy number of sex chromosome genes (Birchler et al 2006;Chang et al 2006;Arnold et al 2008). Dosage compensation mechanisms operate not only to reduce sex bias in expression of sex chromosome genes, but also to reduce the disparity of expressed dose of sex chromosome and autosomal (A) genes (Nguyen and Disteche 2005).…”
mentioning
confidence: 99%
“…The ratios vary gene-by-gene over the length of the Z chromosome. This piecemeal pattern of compensation differs from the three most thoroughly studied examples of sex chromosome dosage compensation-flies, worms and mammals (Birchler et al, 2006)-in which there is a greater percentage of X-linked genes that are compensated, in these cases in males.…”
mentioning
confidence: 62%
“…Recent studies have indicated a common theme in these three taxa. In each case, there is a two-fold upregulation of the single X chromosome despite the differences in sex-specific chromatin modifications that are unique to each species (Gupta et al, 2006;Nguyen and Disteche, 2006;Birchler et al, 2006). Indeed, triple X metafemales in flies show dosage compensation that requires a downregulation to achieve expression similar to that in normal females (Birchler et al, 1989) and there are no known chromatin differences in this sex chromosome between aneuploid and diploid females.…”
mentioning
confidence: 99%